Dry Taps? A Synthesis of Alternative "Wash" Methods in the Absence of Water and Sanitizers in the Prevention of Coronavirus in Low-Resource Settings - Lucy W. Kivuti-Bitok; Angeline Chepchirchir; Peter Waithaka; Irene Ngune (SAGE Publishing, 2020)
Objective: Social distancing and hand washing with soap and water have been advocated as the main proactive measures against the spread of coronavirus. We sought to find out what other alternative materials and methods would be used among populations without running water and who may not afford alcohol-based sanitizers. Results: We reviewed studies that reported use of sand, soil, ash, soda ash, seawater, alkaline materials, and sunlight as possible alternatives to handwashing with soap and water. We identified the documented mechanism of actions of these alternative wash methods on both inanimate surfaces and at cellular levels. The consideration of use of these alternative locally available in situations of unavailability of soap and water and alcohol-based sanitizers is timely in the face of coronavirus pandemic. Further randomized studies need to be carried out to evaluate the effectiveness of these alternatives in management of SARS-Cov-2.